A system to monitor statin-induced myopathy in individual engineered skeletal muscle myobundles. Issue 18 (16th August 2018) - Zhang, Xu; Hong, Sungmin; Yen, Ringo; Kondash, Megan; Fernandez, Cristina E.; Truskey, George A.
Abstract : Microphysiological tissue engineering models of human skeletal muscle (myobundles) in series with a calibrated elastic membrane provide a platform to investigate the mechanism of muscle diseases and to study the response to drugs and toxins in vitro . Abstract : Microphysiological tissue engineering models of human skeletal muscle (myobundles) provide a platform to investigate the mechanism of muscle diseases and to study the response to drugs and toxins in vitro . To examine the dynamic response to drugs, which often take several days to induce responses, we developed a system to monitor the contractile force of the same human skeletal muscle myobundles over time before and after treatment with drugs. Myobundles were formed in series with Ecoflex films (platinum-catalyzed silicones) with embedded microbeads. The displacement of the microbeads in Ecoflex exhibited a linear relation between muscle force production and Ecoflex film stretch. Forces measured with the microbeads embedded in Ecoflex agreed well with simultaneous measurements with a force transducer. Application of the Hill model for the myobundles showed that the Ecoflex affected the magnitude of the response, but not the kinetics. After continuous exposure to 100 nM cerivastatin, both active and passive forces were reduced relative to controls after 2–4 days. The decline in force was associated with a decline in the muscle myofiber organization. The inhibitory effect of cerivastatin was reduced when 0.1–1 mM mevalonate was added with cerivastatin. Although addition of co-enzyme Q10 with cerivastatin inhibited degradation of sarcomeric α-actinin (SAA) in myoblasts, the contractile force still declined, suggesting that statin-induced myopathy was related to mevalonate pathway but the addition of co-enzyme Q10 was insufficient to overcome the effect of statins on the mevalonate pathway. Thus, cerivastatin rapidly induces myopathy which can be reversds with mevalonate but not co-enzyme Q10.